The Role of Online Peer Support Forum in Coping with Diabetes: A Narrative Analysis - Liu, Shuai (International Journal of Humanities and Social Science, 2026)
This study investigates how diabetes patients construct and share their experiences within an online peer support forum, focusing on the narratives they use to make sense of their condition and cope with its challenges. Using posts from the Sweet Home Diabetes Forum as data, this research employs a narrative analysis framework to identify four predominant narrative types: self-acceptance, education, lifestyle modifications, and social support. The self-acceptance narrative highlights patients' journeys toward acknowledging their diagnosis, building mental resilience, and maintaining a positive outlook. The education narrative emphasizes the importance of acquiring knowledge about diabetes, sharing information, and utilizing diverse resources to better manage the condition. The lifestyle modifications narrative reflects personal efforts to adapt through changes in diet, exercise, medication routines, and glucose monitoring, fostering a sense of control. Finally, the social support narrative underscores the role of family, friends, and online communities in providing emotional encouragement, practical advice, and a sense of belonging. These narratives demonstrate how diabetes patients navigate their experiences, reconstruct their identities, and foster connection through storytelling. The findings underscore the therapeutic value of online forums, offering insights for healthcare professionals to better support patients' emotional and social needs.